Deep inelastic scattering from polarized spin-1/2 hadrons at low x from string theory - Kovensky, Nicolas (2018)
We study polarized deep inelastic scattering of charged leptons from spin-1/2 hadrons at low values of the Bjorken parameter and large ?t Hooft coupling in terms of the gauge/string theory duality. We calculate the structure functions from type IIB superstring theory scattering amplitudes. We discuss the role of the non-Abelian Chern-Simons term and the Pauli term from the five-dimensional SU(4) gauged supergravity. Furthermore, the exponentially small-x regime where Regge physics becomes important is analyzed in detail for the antisymmetric structure functions. In this case the holographic dual picture of the Pomeron exchange is realized by a Reggeized gauge field. We compare our results with experimental data of the proton antisymmetric structure function g1, obtaining a very good level of agreement.